Eksplorasi Air Tanah di Daerah Bakarangan, Kec. Kusan Hulu, Kab. Tanah Bumbu, Kalimantan Selatan - Ashady Adhe; Waterman SB; Nurkhamim (Retii, 2022)
Groundwater is water that flows in the sub-surface where the formation is called aquifer. The groundwater can be found tens or even hundreds of meters below the surface. On the other hand, layers that allow water to pass easily are called permeable layer, but impermeable has no ability to pass the water. Gravel, sand, pumice, and cracked rock are examples of the permeable. Clay or loam layers are examples for impermeable layer. Furthermore, according to its location, groundwater can be divided into shallow groundwater (phreatic groundwater) and deep groundwater (aresthetic groundwater). The shallow groundwater located above an impermeable layer with depth of 15 to 40 meters. The deep groundwater is commonly found between two impermeable layers with depth of more than 40 meters. This paper focused on the ground water exploration through resistivity geoelectric method. Moreover, the configuration in the method used was Schlumberger and Wenner-Schlumberger configuration. The combination of these two configurations provided a relatively high resolution picture finding the aquifer for both horizontally and vertically.